1983
DOI: 10.1097/00000658-198304000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Surgery, Trauma and Immune Suppression Evolving the Mechanism

Abstract: A major surgical procedure can impair the delayed hypersensitivity response. This impairment is associated with suppressor cell activity that can alter either afferent or efferent responses. Using the third party mixed leukocyte culture to define cell types involved, major immune impairment was seen with the combination of both nonadherent and plastic adherent cells, suggesting that a T cell-macrophage interaction is required. A serum factor(s) is present in operated mice that can impair mixed leukocyte cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 14 publications
0
28
0
1
Order By: Relevance
“…Perioperative complications can lead to a modulation of the immune state, decrease in tumor surveillance, and possibly increased risk of disease recurrence and disease-specific death. [12][13][14][15] To the best of our knowledge, the current study is the first to examine the association between the occurrence of a postoperative complication and long-term outcomes among patients undergoing hepatic resection for ICC. The current study is important because the data have demonstrated that postoperative complications were independently associated with both RFS and OS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perioperative complications can lead to a modulation of the immune state, decrease in tumor surveillance, and possibly increased risk of disease recurrence and disease-specific death. [12][13][14][15] To the best of our knowledge, the current study is the first to examine the association between the occurrence of a postoperative complication and long-term outcomes among patients undergoing hepatic resection for ICC. The current study is important because the data have demonstrated that postoperative complications were independently associated with both RFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…Laparotomy itself can initiate a systemic inflammatory response characterized by high levels of inflammatory cytokines and C-reactive protein. 13,14,34 Colacchio et al reported that perioperative stress can depress natural killer cell cytotoxicity and increase tumor burden. 35 For example, in an animal model, these investigators compared animals who did and did not have surgical stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of tumor cells can potentially inhibit host immunity through various mechanisms such as the production of immunosuppressive IL-10 [9]. In addition, conventional chemotherapy [44], radiotherapy [21], and surgery [4,24] frequently suppress host immunity; therefore, cancer patients are generally, immunologically suppressed.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, either the total [3,4] and the T-cell [5,6] lymphocytopenia represents a prognostic factor for a poor survival in cancer patients, independent by other well known clinical prognostic factors such as performance status, disease extent, and weight loss [4,7]. Moreover, although radical surgery represents the only curative treatment, the biological response to major surgical trauma induces a temporary immunosuppression, likely due to the release of polipeptidic mediators having immunosuppressive activity [8] and to the direct inhibition of circulating lymphocytes by monocytes/macrophages [9] induced by laparotomic surgical stress [10].…”
Section: Introductionmentioning
confidence: 99%